Strengthening the Strong Program in Cultural Sociology - Lidz, Victor (Honorary Doctorate Lecture Series, 2019)
Victor Meyer Lidz is today's most eminent scholar in the field of action theory in the tradition of the work of Talcott Parsons. His presence at our university as a teacher and collegial research collaborator has significantly contributed to the international visibility and reputation of our Faculty of Social and Political Sciences as a center for social theory. In 2017, he was awarded an honorary doctorate of our university. The volume contains the speech he delivered, the laudatio held by Prof. Jeremy Tanner, University College London, and a comprehensive bibliography of the publications of Victor M. Lidz. - Victor Meyer Lidz ist der heute bedeutendste Wissenschaftler im Bereich der Handlungstheorie in der Tradition von Talcott Parsons. Seine Präsenz an unserer Universität als Dozent und wissenschaftlicher Mitarbeiter hat maßgeblich zur internationalen Sichtbarkeit und zum Ruf unserer Fakultät für Soziale und Politische Wissenschaften als Zentrum für Sozialtheorie beigetragen. 2017 wurde ihm die Ehrendoktorwürde unserer Universität verliehen. Dieser Band beinhält die von ihm gehaltene Rede, die laudatio von Prof. Jeremy Tanner, University College London, und eine umfassende Publikationsbibliographie von Victor M. Lidz.